Conceptual Design of Experimental Facility for Large-Diameter NTD-Si at the IRT-T Reactor - Lebedev I. I. Ivan Igorevich; Zolotykh D. E. Daniil Evgenjevich; Naymushin A. G. Artem Georgievich; Smolnikov N. V. Nikita Viktorovich; Anikin M. N. Mikhail Nikolaevich; Varlachev V. A. Valery Aleksandrovich (2021, 2021)
Title screen